Optimization of HB-UWB Transmission Waveform for BAN Applications - Chaisang, Aditep; Promwong, Sathaporn (My University, 2018)
The modern technology of wireless communications is rapidly developed and apply with short range communication networks around human body. The related research in these application has been investigating. In order to study the effect of human body in the high speed data rate technology, the patterns of ultra wideband for body area network has been studied. The measurement results have been measure and collected by vector network analyzer and analyze by using the equation of Friis. The proposed model is design for test and measure with human body in an indoor environment. The results show the usefulness information for a wireless communication for human body area network with ultra wideband.
Keywords: BAN; Friis's transmission formula; Impulse radio; UWB; WBAN